2009
DOI: 10.1021/ma900016w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Weight on Hydrated Morphologies of the Short-Side-Chain Perfluorosulfonic Acid Membrane

Abstract: We have carried out dissipative particle dynamics (DPD) simulations in an attempt to better understand how molecular weight (MW) affects the hydrated morphology of the short-side-chain (SSC) perfluorosulfonic acid (PFSA) fuel cell membrane. Previously, we demonstrated that such coarse-grained simulations are capable of revealing differences in the morphology of PFSA membranes when either the length of the side chain or equivalent weight (EW) of the ionomer is changed [Wu et al. Energy EnViron. Sci. 2008, 1, 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
158
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(173 citation statements)
references
References 81 publications
(191 reference statements)
13
158
1
Order By: Relevance
“…Averaging over the configurations generated for the CG model revealed that connectivity of the water domains occurs at relatively low water content, viz., at k* % 9. This value is noticeably lower than that estimated in the DDFT [20] and DPD [32] simulations of Nafion (k* % 16). It should be noted that percolating cluster at and just beyond the percolation point coexists with a small fraction of isolated (smaller) aggregates.…”
Section: Resultscontrasting
confidence: 61%
“…Averaging over the configurations generated for the CG model revealed that connectivity of the water domains occurs at relatively low water content, viz., at k* % 9. This value is noticeably lower than that estimated in the DDFT [20] and DPD [32] simulations of Nafion (k* % 16). It should be noted that percolating cluster at and just beyond the percolation point coexists with a small fraction of isolated (smaller) aggregates.…”
Section: Resultscontrasting
confidence: 61%
“…There has been controversy regarding the morphology of the water network as numerical and experimental investigation of the microstructure of Nafion and related PFSA membanes have lead to the proposition of bi-layer morphologies [42,43], cylindrical pores [44], an inverted pore morphology with solvent groups surrounding cylinders of crystallized backbone [6,45], spherical clusters [39], as well as more complex morphologies suggested by atomistic simulations [3,35,46,47]. Regarding the crystalline domains, proposed models include lamellar models [48], the rod-like model [45], a fringed-micelle model [40], and bi-modal networks [49].…”
Section: A Study Of Nafion: Comparison To Saxs Datamentioning
confidence: 99%
“…By virtue of their tethered charges, these networks are selectively conductive, inhibiting the transport of co-ions while facilitating the transport of counter-ions. The broad class of ionomer membranes have important applications in efficient energy conversion devices such as polymer electrolyte membranes for fuel cells [3][4][5][6], dye sensitized solar cells [7], bulk-heterojunction solar cells [8,9], and lithium ion batteries [1,10,11]. Considerable computational and experimental effort has been invested in the design and optimization of membranes with strongly charge-selective transport characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…A simpler route for the synthesis of SSC ionomer was developed and marketed under the trade name Aquivion ® (previously Hyflon ® ) by Solvay Solexis [12]. SSC-PFSA ionomer membranes (PEMs) have been previously characterised ex situ and in fuel cells [10,[13][14][15], as have theoretical studies aiming to explain the morphology of SSC-PFSA as a function of IEC [16,17]. The development of new ionomers to replace Nafion as a membrane has led to the incorporation of new ionomers in the catalyst layer.…”
Section: Introductionmentioning
confidence: 99%